Economic evaluation of the OSAC randomised controlled trial: oral corticosteroids for non-asthmatic adults with acute lower respiratory tract infection in primary care. Issue 2 (18th February 2020) - Moure-Fernandez, Aida; Hollinghurst, Sandra; Carroll, Fran E; Downing, Harriet; Young, Grace; Brookes, Sara; May, Margaret; El-Gohary, Magdy; Harnden, Anthony; Kendrick, Denise; Lafond, Natasher; Little, Paul; et al.
Abstract : Objective: To estimate the costs and outcomes associated with treating non-asthmatic adults (nor suffering from other lung-disease) presenting to primary care with acute lower respiratory tract infection (ALRTI) with oral corticosteroids compared with placebo. Design: Cost-consequence analysis alongside a randomised controlled trial. Perspectives included the healthcare provider, patients and productivity losses associated with time off work. Setting: Fifty-four National Health Service (NHS) general practices in England. Participants: 398 adults attending NHS primary practices with ALRTI but no asthma or other chronic lung disease, followed up for 28 days. Interventions: 2× 20 mg oral prednisolone per day for 5 days versus matching placebo tablets. Outcome measures: Quality-adjusted life years using the 5-level EuroQol-5D version measured weekly; duration and severity of symptom. Direct and indirect resources related to the disease and its treatment were also collected. Outcomes were measured for the 28-day follow-up. Results: 198 (50%) patients received the intervention (prednisolone) and 200 (50%) received placebo. NHS costs were dominated by primary care contacts, higher with placebo than with prednisolone (£13.11 vs £10.38) but without evidence of a difference (95% CI £3.05 to £8.52). The trial medication cost of £1.96 per patient would have been recouped in prescription charges of £4.30 per patient overall (55% participants would have paid £7.85), giving an overall mean 'profit' to the NHS of £7.00 (95% CI £0.50 to £17.08) per patient. There was a quality adjusted life years gain of 0.03 (95% CI 0.01 to 0.05) equating to half a day of perfect health favouring the prednisolone patients; there was no difference in duration of cough or severity of symptoms. Conclusions: The use of prednisolone for non-asthmatic adults with ALRTI, provided small gains in quality of life and cost savings driven by prescription charges. Considering the results of the economic evaluation and possible side effects of corticosteroids, the short-term benefits may not outweigh the long-term harms. Trial registration numbers: EudraCT 2012-000851-15 and ISRCTN57309858 ; Pre-results.